COST ACCOUNTING CONCEPTS. - Read, W. H.; Stanford, Clement L.; Kendricx, H. W.; Dixon, Robert L. (The Accounting Review, 1948)
Abstract The art of accounting including cost accounting, consists primarily of accounting methods which may be described as procedures or practices. However, a comprehensive statement of cost accounting necessitates that one look behind the accounting methods and see upon what ground the whole system of cost accounting is constructed. Cost accounting concepts, as well as concepts of general accounting, may be divided into two groups: first, those ideas having to do with the nature and purpose to the organization which cost accounting. is to serve; second, those ideas as to the purpose and function of cost accounting in rendering its services to the organization. Cost accounting consists of those phases of accounting in general which have to do with the classification and assignment of costs to centers of operation, to product units, and to portions of the revenue stream. In addition it includes the reporting of all types of cost information. Within its scope are the accounting techniques which seek to determine the over all periodic net income of the business firm as well as the portions of that income derived from divisions, departments, product lines, or other subdivisions of the business enterprise.